3*d=6

Simple and best practice solution for 3*d=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3*d=6 equation:


3*d=6

We simplify the equation to the form, which is simple to understand
3*d=6

Simplifying:
+3d=6

We move all terms containing d to the left and all other terms to the right.
+3d=+6

We simplify left and right side of the equation.
+3d=+6

We divide both sides of the equation by 3 to get d.
d=2

See similar equations:

| -2(x+5)=3(x-2) | | 17.50d=125.00 | | r^2+6r=20+7r | | 6=2m+4 | | 2*x=4*2x | | 2x+21=9x+49 | | -30=4x-14 | | 2a^2+1=149 | | -4t^2+2t+1=0 | | 2x+-2=4+x | | 4(3b-1)=16 | | 17=n-9 | | x-2=4+x | | 17.50d=125 | | -7+n=2 | | 9(z-8)=10z-7 | | 2u+20=100 | | x^2-15x+56.25=8 | | 2x+3x^2=2x+3y | | 3x-=x+5 | | 4a=3a-14 | | 7x=5x+14 | | (4)X+24=36 | | 2x+3x^2=33 | | -6y+17=3y+10 | | 12x+4=4x+28 | | 10x+-8=28 | | 4(3-x)=-3 | | 36=14+x/2 | | 4-6x+6+-3=93 | | 12=4z-8 | | -4x+5=27 |

Equations solver categories